Increased prevalence of methicillin-resistant Staphylococcus aureus nasal colonization in household contacts of children with community acquired disease - Rafee Yaseen; Abdel-Haq Nahed; Asmar Basim; Salimnia Tanaz; Pharm Celine; Rybak Pharm Michael J; Amjad Muhammad (BMC Infectious Diseases, 2012)
Abstract Background To measure Methicillin-resistant Staphylococcus aureus (MRSA) nasal colonization prevalence in household contacts of children with current community associated (CA)-MRSA infections (study group) in comparison with a group of household contacts of children without suspected Staphylococcus aureus infection (a control group). Methods This is a cross sectional study. Cultures of the anterior nares were taken. Relatedness of isolated strains was tested using pulse field gel electrophoresis (PFGE). Results The prevalence of MRSA colonization in the study group was significantly higher than in the control group (18/77 (23%) vs 3/77 (3.9%); p ≤ 0.001). The prevalence of SA colonization was 28/77 (36%) in the study group and 16/77 (21%) in the control group (p = 0.032). The prevalence of SA nasal colonization among patients was 6/24 (25%); one with methicillin-susceptible S. aureus (MSSA) and 5 with MRSA. In the study (patient) group, 14/24 (58%) families had at least one household member who was colonized with MRSA compared to 2/29 (6.9%) in the control group (p = 0.001). Of 69 total isolates tested by PFGE, 40 (58%) were related to USA300. Panton-Valetine leukocidin (PVL) genes were detected in 30/52 (58%) tested isolates. Among the families with ≥1 contact colonized with MRSA, similar PFGE profiles were found between the index patient and a contact in 10/14 families. Conclusions Prevalence of asymptomatic nasal carriage of MRSA is higher among household contacts of patients with CA-MRSA disease than control group. Decolonizing such carriers may help prevent recurrent CA-MRSA infections.